Self-transcendence and its relationship to social rejection among kindergarten teachers (Journal of the College of Basic Education, 2026)
The current research aims to identify self-transcendence among kindergarten teachers, identify social rejection among kindergarten teachers, and identify the strength and direction of the relationship between self-transcendence and social rejection among kindergarten teachers. The researchers used the descriptive correlational approach. To achieve the objectives of the research, two scales were required to measure self-transcendence and social rejection of kindergarten teachers. The researchers adopted the self-transcendence scale (Al-Fatlawi, 2021) based on Fromm’s theory and consisting of (38) paragraphs distributed over (4) areas. The researchers prepared a scale for social rejection based on Leary’s theory and the scale consisted of (29) paragraphs. The research sample consisted of (200) female kindergarten teachers in the Najaf Education Directorate, who were selected using a stratified random method. The researchers verified the psychometric properties of the two scales. By using statistical methods to process the data using the SPSS statistical package, the following results were reached: Kindergarten teachers have a high degree of self-transcendence and kindergarten teachers do not suffer from social rejection, in addition to the existence of an inverse relationship between self-transcendence and social rejectio.